2015
DOI: 10.1007/s00439-015-1622-x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of 5-ethynyl-2′-deoxyuridine (EdU) as a novel strategy for identification of the skewed X inactivation pattern in balanced and unbalanced X-rearrangements

Abstract: X-chromosome inactivation occurs randomly in normal female cells. However, the inactivation can be skewed in patients with alterations in X-chromosome. In balanced X-autosome translocations, normal X is preferentially inactivated, while in unbalanced X alterations, the aberrant X is usually inactivated. Here, we present a novel strategy to verify the skewed X inactivation pattern through the incorporation of 5-ethynyl-2'-deoxyuridine (EdU) into cells, in 11 patients: five carriers of balanced X-autosome transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…22 However, XLID genes with female phenotypes only in X:autosome translocations is a notable exception to the above observations, and in these cases specifically, skewing of XI is a well-documented phenomenon believed to occur in order to ensure the correct gene dosage of the autosomal segment. 23 This study supports these findings with all cases of X:autosome translocations reported here having skewed XI.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…22 However, XLID genes with female phenotypes only in X:autosome translocations is a notable exception to the above observations, and in these cases specifically, skewing of XI is a well-documented phenomenon believed to occur in order to ensure the correct gene dosage of the autosomal segment. 23 This study supports these findings with all cases of X:autosome translocations reported here having skewed XI.…”
Section: Resultssupporting
confidence: 89%
“…While these numbers are higher than the reported prevalence of skewing in normal non‐carrier females (3.6%), it does not appear that skewed XI favoring expression of the variant allele in affected females or favoring expression of the normal allele in non‐affected carriers explains female phenotypic expression patterns in the majority of XLID syndromes . However, XLID genes with female phenotypes only in X:autosome translocations is a notable exception to the above observations, and in these cases specifically, skewing of XI is a well‐documented phenomenon believed to occur in order to ensure the correct gene dosage of the autosomal segment . This study supports these findings with all cases of X:autosome translocations reported here having skewed XI.…”
Section: Discussionmentioning
confidence: 99%
“…For patient 1, breakpoint localization was performed by fluorescence in situ hybridization (FISH) and array painting as described (Liehr, Heller, Starke, & Claussen, ; Moyses‐Oliveira et al., ) and validated by FISH using bacterial artificial chromosome probe CTD‐3066N24 (Thermo Fisher Scientific, Waltham, MA, USA) and whole‐genome sequencing. X‐chromosome inactivation was assessed as described (Sisdelli et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…The X‐chromosome inactivation pattern was determined by human androgen receptor assay (HUMARA), as previously described by [Araujo and Ramos, ] and modified by [Sisdelli et al, ]. HUMARA was performed in the patient and her mother in order to determine the inactivation pattern in both and the parental origin of the inactive X‐chromosome in the proposita.…”
Section: Methodsmentioning
confidence: 99%